The Impact of Torque on Assessment of Syndesmotic Injuries Using Weightbearing CT Scans: A Cadaver Study. Issue 4 (16th October 2019) - Barg, Alexej; Weinberg, Maxwell W.; Davidson, Nathan P.; Hintermann, Beat; Saltzman, Charles L.; Krähenbühl, Nicola
Category: Ankle, Basic Sciences/Biologics, Trauma Introduction/Purpose: Injury to the distal tibio-fibular syndesmosis can occur as an isolated ligamentous injury or can be associated with bony ankle trauma. The missed diagnosis of such injuries is believed to lead to chronic pain and early degeneration. Weightbearing CT (WBCT) has increased in popularity among foot and ankle surgeons as it offers an accurate representation of joint alignment under weightbearing conditions. However, the use of this imaging modality to diagnose syndesmotic injuries has not been investigated. The purpose of this study was to assess the influence of torque on the assessment of syndesmotic injuries using axial CT images under weightbearing conditions. We hypothesized that torque application would improve the ability to detect syndesmotic injuries. Methods: Seven pairs of male cadavers (tibia plateau to toe-tip) were included. CT scans with axial load application (85 kilograms, kg) and with (10 newton meters, Nm) or without torque to the tibia (corresponding to external rotation of the foot and ankle) were taken during four test conditions. First, intact ankles (Native) were scanned. Second, one specimen from each pair underwent anterior inferior tibio-fibular ligament (AITFL) transection (Condition 1A) while the contralateral underwent deltoid transection (Condition 1B). Third, the lesions were reversed on the same specimens and the remaining intact deltoid or AITFL was transected (Condition 2). Finally, the distal tibiofibular interosseous membrane (IOM) was transected in all ankles (Condition 3). Eight different measurements were performed to assess the integrity of the distal tibio-fibular syndesmosis on axial CT scans. Results: Torque impacted axial CT scan measurements in almost all conditions (Table I). The ability to diagnose syndesmotic injuries using axial CT measurements improved when torque was applied. No significant syndesmotic morphological change was observed with or without torque for either isolated AITFL or deltoid ligament transection. Conclusion: Low magnitude torque rotational stress application had a notable impact on 2D measurements used to diagnose syndesmotic injuries with axial CT scans (cadaveric model). Two dimensional measurements are not effective to distinguish between single AITFL and single deltoid ligament injuries. Because weightbearing conditions allow for a standardized positioning of the foot while radiographs or CT scans are taken, a combination of axial load and torque application is desirable. Further studies including patients with syndesmotic injuries will be necessary to clarify the clinical potential of WBCT scans with torque applied to identify syndesmotic widening.